2019
DOI: 10.1162/jocn_a_01455
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Neural Correlates of Spatial Context Memory Decline in Healthy Aging

Abstract: Aging is associated with episodic memory decline and alterations in memory-related brain function. However, it remains unclear if age-related memory decline is associated with similar patterns of brain aging in women and men. In the current task fMRI study, we tested the hypothesis that there are sex differences in the effect of age and memory performance on brain activity during episodic encoding and retrieval of face–location associations (spatial context memory). Forty-one women and 41 men between the ages … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 116 publications
9
34
2
Order By: Relevance
“…The B-PLS further identified a distinct network of retrieval-related brain activation in men, where associative retrieval (source hits) correlated with activity in positive salience regions, and object-only retrieval (source failures) correlated with activity in negative salience regions. These findings extend our previous reports of differences in brain activity and brain-behavior correlations during episodic encoding based on sex (Subramaniapillai et al, 2019) and genetic risk factors for AD (Rajah et al, 2017), highlighting sex differences in episodic encoding and retrieval related activity in older adults with family history of AD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The B-PLS further identified a distinct network of retrieval-related brain activation in men, where associative retrieval (source hits) correlated with activity in positive salience regions, and object-only retrieval (source failures) correlated with activity in negative salience regions. These findings extend our previous reports of differences in brain activity and brain-behavior correlations during episodic encoding based on sex (Subramaniapillai et al, 2019) and genetic risk factors for AD (Rajah et al, 2017), highlighting sex differences in episodic encoding and retrieval related activity in older adults with family history of AD.…”
Section: Discussionsupporting
confidence: 89%
“…Together, findings from LV1 and LV2 of our T-PLS analysis indicate that older women and men at risk of AD engage similar brain regions during the encoding and retrieval of old vs. novel objects, and that these regions are comparable to episodic memory-related activity in cognitively healthy older adults. Task These findings extend our previous reports of differences in brain activity and brain-behavior correlations during episodic encoding based on sex (Subramaniapillai et al, 2019) and genetic risk factors for AD (Rajah et al, 2017), highlighting sex differences in episodic encoding and retrieval related activity in older adults with family history of AD.…”
Section: Few Sex Differences In Behavior and Brain Activity Related Tsupporting
confidence: 88%
See 1 more Smart Citation
“…We performed behavioral data analyses on neuropsychological tests and episodic memory task performance using SPSS version 24 with a significance threshold of p = 0.05, Greenhouse-Geisser corrections for sphericity, and Bonferroni corrections for multiple comparisons, where applicable. Because evidence suggests meaningful sex/gender differences in the neural and behavioral correlates of episodic memory and cognition in aging [47][48][49], we also investigated self-reported sex as a factor in our analyses.…”
Section: Behavioral Analysesmentioning
confidence: 99%
“…We performed behavioral data analyses on neuropsychological tests and episodic memory task performance using SPSS version 24 with a significance threshold of p=.05, Greenhouse-Geisser corrections for sphericity, and Bonferroni corrections for multiple comparisons, where applicable. Because evidence suggests meaningful sex/gender differences in the neural and behavioral correlates of episodic memory and cognition in aging (Gur & Gur, 2002;McCarrey, An, Kitner-Triolo, Ferrucci, & Resnick, 2016;Subramaniapillai et al, 2019), we also investigated self-reported sex as a factor in our analyses.…”
Section: Behavioral Analysesmentioning
confidence: 99%